Safety evaluation of the food enzyme endo‐polygalacturonase from the genetically modified Aspergillus luchuensis strain FLYSC - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Vittorio Silano; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2022)
Abstract The food enzyme endo‐polygalacturonase ((1→4)‐α‐d‐galacturonan glycanohydrolase; EC 2.3.1.15), is produced with the genetically modified Aspergillus luchuensis strain FLYSC by Advanced Enzyme Technologies Ltd. The genetic modifications do not give rise to safety concerns. The food enzyme is considered free from viable cells of the production organism and its DNA. The food enzyme is intended to be used in fruit and vegetable processing for juice production. Based on the maximum use level, dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.138 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not raise a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 800 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, results in a margin of exposure of at least 5,800. A search for similarity of the amino acid sequence of the food enzyme to known allergens was made and six matches were found. The Panel considered that, under the intended conditions of use, the risk of allergic sensitisation and elicitation reactions by dietary exposure cannot be excluded for individuals sensitised to cedar or grass pollen or maize. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.